THE IMPACT OF UNBALANCED POWER SUPPLY ON LOAD CURRENTS IN TRANSIENT AND STEADY-STATE OPERATION - Štumberger, Nina; Štumberger, Gorazd; Pintarič, Matej (Journal of Energy Technology, 2023)
The impact of unbalanced power supply voltages on power derating, increases in current values and the heat released from electrical machines and devices is typically analysed in quasi-steadystate operation using sequence components. The ratios between the negative and positive sequence voltage and the homopolar (zero) and positive sequence voltage are used to evaluate the level of voltage unbalance. This paper proposes an extension of this approach that includes subtransient, transient and quasi-steady-state operation of wye (grounded and ungrounded) and delta connected loads, consisting of resistors and magnetically linear and non-linear iron core inductors, which is a novelty. Dommel’s method for dynamic simulation of electrical circuits, based on the modified nodal potential method, time discretisation and implicit numerical integration, is applied to evaluate the impact of unbalanced power supply voltages on load currents. The magnetically non-linear behaviour of the iron core inductors is accounted for by introducing variable dynamic inductances inside Dommel’s method. The integrals of instantaneous values of squared load branch currents values in subtransient, transient and quasi-steady-state operation, determined for different levels of unbalance in supply voltages, are normalised with those calculated for the balanced power supply voltages in quasi-steady-state. The obtained ratios of the integrals are used to implicitly evaluate the impact of unbalance in supply voltages on the increase in released heat due to Joule losses. The proposed approach is generally applicable, while the results are shown for the case study of iron core inductors with magnetically linear and non-linear behaviour.